2012
DOI: 10.2478/s11686-012-0004-y
|View full text |Cite
|
Sign up to set email alerts
|

Digenean parasites of Cariama cristata (Aves, Gruiformes) from Formosa Province, Argentina, with the description of a new species of the genus Strigea

Abstract: A new strigeid digenean, Strigea inflecta sp. nov., is described from the small intestine of the Red-legged Seriema, Cariama cristata (L.) (Gruiformes, Cariamidae) from Formosa Province, Argentina. This species is characterized by having a body plump, a cup-shaped forebody with a large opening, a sacciform hindbody, without a neck region and strongly curved dorsally, a poorly delimited copulatory bursa, wider than longer, a shallow and asymmetrical genital atrium, and a genital cone well delimited from body pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…The family Brachylaimidae consists of seven genera (Lunaschi and Drago, 2012) (Dujardin, 1843) Kruidenier & Gallicchio, 1959Brachylaema Yamaguti, 1958;andBrachylaima (Dujardin, 1843) Yamaguti, 1971. These include species of trematodes parasitizing birds and mammals.…”
Section: Number Of Specimensmentioning
confidence: 99%
“…The family Brachylaimidae consists of seven genera (Lunaschi and Drago, 2012) (Dujardin, 1843) Kruidenier & Gallicchio, 1959Brachylaema Yamaguti, 1958;andBrachylaima (Dujardin, 1843) Yamaguti, 1971. These include species of trematodes parasitizing birds and mammals.…”
Section: Number Of Specimensmentioning
confidence: 99%
“…remarks. Among Neotropical species of Strigea, only five species, Strigea caluri Dubois, 1962, Strigea nugax szidat, 1928, Strigea sphaerocephala (Westrumb, 1823, Strigea elliptica (Brandes, 1888) and Strigea inflecta lunaschi et Drago, 2012, can be compared with Strigea orbiculata sp. n. by having a body plump and vitelline glands extensively distributed throughout the forebody.…”
Section: Methodsmentioning
confidence: 99%
“…Metraterm short, 44 long, surrounded by gland cells. Mature eggs dark brown, thick shelled, asymmetrical, operculated, with small knob at the abopercular end, and with fully developed miracidium, 24-29 × 14-21 (26 × 18 Dujardin, 1843 (Brachylaimidae) in Didelphis albiventris (Lund) and Lutreolina crassicaudata (Desmarest) (Didelphidae) from Chaco and Corrientes Provinces, and Brachylaima yupanquii Freitas, Kohn & Ibáñez, 1967 (Brachylaimidae) in Cariama cristata (L.) (Cariamidae) from Formosa Province, and Urotocus fusiformis McIntosh, 1935 (Leucochloridiidae) in Pteroptochos tarnii (King) (Rhinocryptidae) from Gutiérrez and Mascardi lakes, Río Negro Province (Boero and Boehringer 1967;Boero and Led 1968;Martínez 1986Martínez , 2003Flores et al 2003;Zamparo et al 2003a;Lunaschi and Drago 2012). Zamparo et al (2003b) erected the genus Pojmanskia to contain specimens found parasitizing several species of birds from Costa Rica.…”
mentioning
confidence: 99%